2015
DOI: 10.1080/10615806.2015.1016003
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal relations between workplace bullying, anxiety, and vigor: a two-wave longitudinal study

Abstract: Esta es la versión de autor del artículo publicado en: This is an author produced version of a paper published in:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
55
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 57 publications
(56 reference statements)
3
55
0
Order By: Relevance
“…It is also conceivable that targets of bullying become more anxiety-prone over time due to systematic and long-term exposure to bullying. This notion has been supported by longitudinal studies (Rodriguez-Munoz et al, 2015) albeit not consistently (Nielsen and Knardahl, 2015; Podsiadly and Gamian-Wilk, 2017). The findings are also in line with studies showing a tendency, especially among bullies, to morally justify and to attribute bulling behavior to negative traits of the victim (Thornberg and Jungert, 2014).…”
Section: Discussionmentioning
confidence: 96%
“…It is also conceivable that targets of bullying become more anxiety-prone over time due to systematic and long-term exposure to bullying. This notion has been supported by longitudinal studies (Rodriguez-Munoz et al, 2015) albeit not consistently (Nielsen and Knardahl, 2015; Podsiadly and Gamian-Wilk, 2017). The findings are also in line with studies showing a tendency, especially among bullies, to morally justify and to attribute bulling behavior to negative traits of the victim (Thornberg and Jungert, 2014).…”
Section: Discussionmentioning
confidence: 96%
“…Many studies have shown the negative consequences of bullying on a person's health and well-being (e.g. Bonde et al, 2016;Nielsen et al, 2014;Rodríguez-Muñoz, Moreno-Jiménez, & Sanz-Vergel, 2015).…”
Section: Salutogenic Health Indicator Scale (Shis)mentioning
confidence: 99%
“…Workplace bullying is a long-lasting form of workplace aggression, comprised of repeated, abusive, and offensive acts against which the targets have difficulty defending themselves (Einarsen, 2000). It is a source of major distress at work, with prospective evidence showing that bullying predicts psychological health problems (Einarsen & Nielsen, 2015;Nielsen & Einarsen, 2012), depression (Kivimäki et al, 2003;Tuckey, Dollard, Saebel, & Berry, 2010), anxiety (Rodríguez-Muñoz, Moreno-Jiménez, & Sanz-Vergel, 2015), emotional exhaustion (Laschinger & Fida, 2014), and traumatic stress (Bond, Tuckey, & Dollard, 2010), as well as physical health problems, such as poor cardiovascular health (Kivimäki et al, 2003;Tuckey et al, 2010). Bullying has costly effects (McTernan, Dollard, & LaMontagne, 2013) because of increased employee sickness absence (Ortega, Christensen, Høgh, Rugulies, & Borg, 2011), higher turnover rates (Høgh, Hoel, & Carneiro, 2011), and workers' compensation claims (Bailey, Dollard, McLinton, & Richards, 2015).…”
mentioning
confidence: 99%